The romance of mystery and the mystery of romance: Charlotte Smith's Ethelinde, Wilkie Collins's "I say no," the McGuffin, and narrative closure (Article) - Kale, K. A. (2023)
In this article, I argue that Charlotte Smith’s novel Ethelinde (1789) is structurally similar to Wilkie Collins’s novel “I Say No” (1884). As a consequence, Ethelinde highlights similarities between two of the great genres of formula fiction: the romance and the whodunit. Further, I shall argue that the twentieth-century theory of the McGuffin can complicate generic conventions by showing how a driving narrative force can evade clear categorization as either a McGuffin or not.